2019
DOI: 10.3390/ani9050243
|View full text |Cite
|
Sign up to set email alerts
|

Finding Meanings in Low Dimensional Structures: Stochastic Neighbor Embedding Applied to the Analysis of Indri indri Vocal Repertoire

Abstract: Although there is a growing number of researches focusing on acoustic communication, the lack of shared analytic approaches leads to inconsistency among studies. Here, we introduced a computational method used to examine 3360 calls recorded from wild indris (Indri indri) from 2005–2018. We split each sound into ten portions of equal length and, from each portion we extracted spectral coefficients, considering frequency values up to 15,000 Hz. We submitted the set of acoustic features first to a t-distributed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…
Figure 1Rhythm and social interactions in indris. ( a ) A spectrogram of a vocal interaction between two males from the same family group that compete for food; the adult male emits a low-pitched grunt [84] followed by a kiss and a wheeze from the younger male [85]. ( c ) A spectrogram of part of an unusual solo song by a male indri.
…”
Section: Non-human Primatesmentioning
confidence: 99%
“…
Figure 1Rhythm and social interactions in indris. ( a ) A spectrogram of a vocal interaction between two males from the same family group that compete for food; the adult male emits a low-pitched grunt [84] followed by a kiss and a wheeze from the younger male [85]. ( c ) A spectrogram of part of an unusual solo song by a male indri.
…”
Section: Non-human Primatesmentioning
confidence: 99%
“…Indris ( Indri indri ; Gmelin, 1788) represent a distinctive species for studying vocal communication because of their rich repertoire (Maretti, Sorrentino, Finomana, Gamba, & Giacoma, 2010; Valente et al, 2019) and the impressive loud songs, unique among lemurs (Gamba et al, 2016; Torti et al, 2017), which can be heard at a distance up to 2 km (Pollock, 1986). Data on sound pressure levels revealed that the sound levels of the indri's song reached 110 dB (estimated at 0.50 m; Torti, pers.…”
Section: Introductionmentioning
confidence: 99%
“…The song of the indris, which lasts 40–250 s, consists of a long series of modulated units, organized in phrases (Gamba, Favaro, Torti, Sorrentino, & Giacoma, 2011), uttered simultaneously by males and females, including juveniles, of the same group (Maretti et al, 2010). These types of units are emitted exclusively during the song (Valente et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most unsupervised applications related to non‐human primate vocalizations have investigated species‐specific call repertoires (Keenan et al., 2013; Pozzi et al., 2009; Price et al., 2015; Valente et al., 2019; Wadewitz et al., 2015). One of the foundational applications of unsupervised clustering was used to investigate the vocal repertoire of Barbary macaques Macaca sylvanus (Hammerschmidt & Fischer, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One of the foundational applications of unsupervised clustering was used to investigate the vocal repertoire of Barbary macaques Macaca sylvanus (Hammerschmidt & Fischer, 1998). Since then, unsupervised approaches have been used to investigate vocal repertoires in indris Indri indri (Valente et al., 2019), black lemurs Eulemur macaco (Pozzi et al., 2009), Eulemur spp. (Gamba et al., 2015), marmosets Callithrix jacchus (Turesson et al., 2016), douc langurs Pygathrix cinerea (Riondato et al., 2017), Campbells's monkeys Cercopithecus campbelli (Keenan et al., 2013), chacma Papio ursinus , olive P. anubis and Guinea baboons P. papio (Hammerschmidt & Fischer, 2019) and gorillas Gorilla gorilla (Hedwig et al., 2014).…”
Section: Introductionmentioning
confidence: 99%